Phase shift of terahertz Bloch oscillations induced by interminiband mixing in a biased semiconductor superlattice. (13th March 2019) - Unuma, Takeya; Maeda, Shuhei
Abstract: We investigate terahertz waveforms emitted from a GaAs-based superlattice with interminiband mixing under various dc bias electric fields, injecting electrons into the conduction first miniband with femtosecond optical pulses. Bloch oscillations are observed under relatively low bias fields; surprisingly, the oscillation phase is found to shift by π /2 from those reported previously for Wannier–Stark ladder states in nearly isolated minibands. The oscillatory feature of terahertz emission is gradually destroyed under higher bias fields. We show that the observed π /2 phase shift can be ascribed to significant delocalization of electron wavefunctions driven by interminiband mixing.